Konzept des Bundesrates für eine Sportpolitik in der Schweiz (BASPO, 2000)
In November, 2000 the swiss government, the Bundesamt für Sport, decided a concept for a sports policy in Switzerland. This includes an analysis of the actual situation, aims, demands, finances etc. of a new Swiss sports policy.